Analisis Kandungan Siklamat Pada Minuman Boba Yang Dijual Di Warungasem Kabupaten Batang - Khasanah, Kharismatul; Shella Sya'bana, Nur (LPPM ITEKES Mahardika, 2023)
Boba drink is a high-calorie drink from Taiwan that is currently popular in Indonesia. This drink is categorized as a sweetened drink with the use of artificial sweeteners instead of natural to reduce production costs. The artificial sweetener used is sodium cyclamate because it has 30 times sweetness intensity of sucrose and is relatively cheaper. The use of artificial sweeteners according to BPOM RI regulation No. 11 of 2019 has a maximum limit of 250 mg/kg. This study aims to determine the presence of cyclamate content and the level of cyclamate in boba drinks sold in Warungasem, Batang. This research is a descriptive study with a qualitative and quantitative analysis approach. Samples were obtained from sellers in the Warungasem area of Batang using the saturated sample technique. The samples taken were boba beverage liquid (Code A) and Bola-boba (Code B). The qualitative analysis method used is the precipitation method while the gravimetric method quantitavely. The results showed 50% from 14 samples tested were positive for cyclamate characterized by the presence of white precipitate. Gravimetric quantitative test obtained cyclamate content exceeds the BPOM maximum limit of 250 mg/kg by 28,57% from samples tested, namely codes A4, A5, A6 and A7.